Interest is an attitude of a consumer in the form of willingness to use or try something offered by the company, in the form of products / services. This is influenced by many factors including quality of product / service, location, promotion, com - Nuris Syafaah, 14.05.51.0259; Marlien, Marlien (Students' Journal of Economic and Management, 2018)
Interest is an attitude of a consumer in the form of willingness to use or try something offered by the company, in the form of products / services. This is influenced by many factors including quality of product / service, location, promotion, company image, price perception, etc. The purpose of this study was to analyze the influence of promotion and corporate image on student interest in students at Stikubank University Semarang. The population of this study were students enrolled in Semarang Stikubank University (UNISBANK) Semarang. The sample in this study were 120 respondents. The sampling technique uses non probability sampling. The sampling method uses purposive sampling. The sample criteria in this study were students of Stikubank University (UNISBANK) Semarang. Data processing was carried out using SPSS 19. The analytical tool used was validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test and multiple linear regression. The results of the study can be concluded that: promotion has a positive and significant effect on the interest in college. This means that the better the promotion, it will increase the interest in college. Company image has a positive and significant effect on the interest in college. This means that the better the company's image, it will increase the interest in college. Keywords : Promotion, Corporate Image, and college Interest.